The King Sitting Backward in His Chariot: A Ramesside Icon of Victory - Sabbahy, Lisa.
Ramesside Period kings covered temple walls with decorative relief detailing their military expeditions and subsequent victories. Included in these reliefs were new types of scenes with new details, including one scene in which the king sits backward in his chariot, receiving live captives and cut off body parts as proof of his victory. This article presents the evidence for this particular chariot scene, and discusses the meaning and use of it as an icon of victory.